DETERMINATION OF FAECES PARTICLE PROPORTIONS AS A TOOL FOR THE EVALUATION OF THE INFLUENCE OF FEEDING STRATEGIES ON FIBRE DIGESTION IN DAIRY COWS - F. Leiber; S. Ivemeyer; E. Perler; I. Krenmayr; P. Mayer; M. Walkenhorst (Journal of Animal and Plant Sciences, 2015)
Aim of this study was to test the influence of feeding strategy on faecal particle size distribution as indicator of fibre digestion under on-farm conditions. Seventy-six cows from 11 farms, located in Switzerland and southern Germany were included. Cows were monitored up to eight times during one full lactation. All valid individual test days resulted in a total of 347 datasets. Milk yield and composition were recorded. Diet composition was described in a binary yes/no-indication for the presence or non-presence of different roughage components (fresh grass, grass silage, hay, maize silage and straw) and the exact amount of concentrates. Faecal samples were taken at each test day and sieved with a set of four wire‐mesh screens with pore sizes of 4mm, 2mm, 1mm, and 0.3mm under running tap water. Dry matter proportions were calculated. The inclusion of maize silage and an increasing level of concentrates significantly increased the presence of faecal particles in the sieves. Maize silage increased the larger particles, while concentrates enhanced the smaller particle fractions. No effect of fresh grass and grass silage was found. Based on the results, the faecal particle fractions appear to be a practicable tool to predict influences of feeding systems on fibre utilization in dairy cows.
Keywords: Dairy cattle; feeding system; forage; faeces; fibre utilization